African Swine Fever Virus p72 Genotype IX in Domestic Pigs, Congo, 2009 - Gallardo, C.; Anchuelo, R.; Pelayo, V.; Poudevigne, F.; León, T.; Nzoussi, J.; Bishop, Richard P.; Pérez, C.; Soler Garzón, Alvaro; Nieto, R.; Martín, H.; Arias, Marisa (Centers for Disease Control and Prevention, 2011)
African swine fever virus p72 genotype IX, associated with outbreaks in eastern Africa, is cocirculating in the Republic of the Congo with West African genotype I. Data suggest that viruses from eastern Africa are moving into western Africa, increasing the threat of outbreaks caused by novel viruses in this region.